Phosphorus recovery through struvite crystallization from real wastewater: Bridging gaps from lab to market - Yan, Yixin; Kallikazarou, Nomiki; Nisiforou, Olympia A.; Shang, Qingyu; Fu, Dafang; Antoniou, Maria G.; Fotidis, Ioannis A. (My University, 2025)
Food security will be jeopardized as reserves of the non-renewable phosphate rock, which is used to manufacture phosphorus fertilizers, are rapidly depleting. Meanwhile, excess nutrient (phosphorus and nitrogen) loads coming from improperly treated nutrient-rich wastewaters are disposed in soil and water resources, and significantly affect the atmosphere, lithosphere, hydrosphere and biosphere. Struvite crystallization (SC) offers a promising solution, recovering nutrients as a slow-release fertilizer. However, SC's application across various wastewater types remains limited, with few full-scale implementations. This review examines SC process, focusing on studies using real wastewaters. Key SC methodologies include chemical, electrochemical, ion-exchange precipitation, membrane crystallization, and microbial mineralization. Wastewater pretreatment methods are classified and critically evaluated, while SC-affecting factors like calcium and salinity are discussed. To enhance SC's economic sustainability, future research should prioritize cost-efficient reactor designs, energy recovery strategies, and regulatory compliance to develop market-ready, waste-derived fertilizers that are safe for agricultural applications.
Keywords: Pretreatments; Nutrients; Operating conditions; Organo-mineral fertilizer; Post-harvest processes